Trends in ChatGPT and Generative Artificial Intelligence in Education Research: A Scopus Based Analysis - Miftahul Jannah; Benny Prasetiya; Febry Suprapto; Khoiriyah (PT. Caesarindo Triloka Persada, 2026)
The emergence of Generative Artificial Intelligence (GenAI) technologies such as ChatGPT has transformed the landscape of education research, reshaping how knowledge is created, accessed, and disseminated. This study aims to analyze global research trends on ChatGPT and GenAI in education through a bibliometric analysis of Scopus-indexed publications from 2023 to 2025. Using a quantitative bibliometric approach with data visualization tools such as VOSviewer and Bibliometrix (R package), this research examines publication growth, scientific collaboration, influential authors and journals, and keyword co-occurrence networks. The PRISMA 2020 protocol was applied to ensure systematic and transparent data selection. The results show an exponential increase in research output on GenAI in education, with the United States, China, and Australia leading contributions. Thematic mapping reveals three dominant clusters: (1) ChatGPT and generative AI applications in higher education; (2) human-centered and ethical AI in learning; and (3) large language models (LLMs) in educational innovation. This study identifies ChatGPT as both a learning tool and an epistemic partner that enhances personalization, creativity, and efficiency in teaching and research. The novelty of this research lies in its development of the “Generative Education Ecosystem (GEE)” framework, integrating socio-technical systems and constructivist theories to explain human-AI collaboration in learning. The findings contribute empirically and theoretically to understanding the global trajectory of GenAI in education and provide strategic insights for policymakers and educators to foster adaptive, ethical, and sustainable AI-based learning systems.